Eucommia ulmoides Oliv. and its bioactive compounds: therapeutic potential in bone diseases - Huang, Cai; Jin, Huan; Zhang, Yan; Wang, Di; He, Ziyi; Shuai, Bo (Frontiers in Pharmacology, 2025)
BackgroundAging-related bone diseases encompass a range of conditions that emerge or worsen with advancing age, including osteoporosis and osteoarthritis, and they are placing an increasing burden on society. Although these diseases differ in clinical manifestations and pathological features, they often share common age-associated mechanisms such as impaired bone remodeling, chronic low-grade inflammation, cellular senescence, oxidative stress, and hormonal changes. Current therapies often face limitations in efficacy or long-term safety, highlighting the need for alternative strategies. Phytochemicals derived from Chinese medicine herb have emerged as promising candidates due to their multi-target effects on bone homeostasis. Eucommia ulmoides Oliv. (EU) and its bioactive compounds (e.g., quercetin, aucubin, geniposide, geniposidic acid). may regulate key pathways to restore bone balance, offering potential for treating osteoporosis and other aging-related bone diseasesObjectivesThis study aims to assess the therapeutic potential of EU in the treatment of aging-related bone diseases.MethodsA literature search was conducted on the PubMed database up to November 2024 using the search term: “Eucommia AND (bone OR cartilage OR joint).”ResultsThe review indicates that EU formulas, extracts, and bioactive components promote osteogenesis, suppress bone resorption, and exert anti-inflammatory and antioxidant properties. These effects contribute positively to the treatment of aging-related bone diseases.ConclusionThe therapeutic benefits of EU support its development as a promising tool for preventing and treating aging-related bone diseases. These findings provide new research directions to address related health challenges associated with population aging.